An Introduction to the Study of Mineralogy - Aydinalp, Cumhur (IntechOpen, 2012)
An Introduction to the Study of Mineralogy is a collection of papers that can be easily understood by a wide variety of readers, whether they wish to use it in their work, or simply to extend their knowledge. It is unique in that it presents a broad view of the mineralogy field. The book is intended for chemists, physicists, engineers, and the students of geology, geophysics, and soil science, but it will also be invaluable to the more advanced students of mineralogy who are looking for a concise revision guide.